The Effect of Local Government Characteristics on Performance of Local Government Administration - Utama, Fikri Rizki; Evana, Einde; Gamayuni, Rindu Rika (International Research Journal of Business Studies, 2019)
This study aimed to obtain empirical evidence of the level of regional wealth, the level of dependence to the central government, capital expenditure contribution and legislature size on the performance of local government administration. This research used a purposive sampling method. The study sample consisted of 293 LKPD provinces, districts, municipalities in Indonesia in 2015 which have been audited by the Supreme Audit Board. The result of the research shown that the variables of legislative size had a positive and significant effect on the performance of local government administration while the level of regional wealth, dependency level to the central government and capital expenditure contribution had no significant effect on the performance of the local government.